Research and Engineering Practice of Var-Voltage Control in Primary and Distribution Networks Considering the Reactive Power Regulation Capability of Distributed PV Systems - Haiyun Wang; Qian Chen; Linyu Zhang; Xiyu Yin; Zhijian Zhang; Huayue Wei; Xiaoyue Chen (Energies)
To fully utilize the reactive power resources of distributed photovoltaic (PV) systems, this study proposes a coordinated var-voltage control strategy for the main distribution network, incorporating the reactive power regulation capability of distributed PV. Firstly, the Automatic Voltage Control (AVC) tertiary and secondary voltage control methods and optimization models in the main and distribution networks area are analyzed, and the physical equivalence of the reactive power compensation equipment involved is carried out. In this study, a coordinated local var-voltage control method is proposed, which integrates AVC primary voltage control and divides the control scheme into feeder and station areas, respectively. Through the analysis of actual operation cases in a regional power grid, the results demonstrate a reduction in network loss by 171.14 kW through voltage adjustment, validating the effectiveness of the proposed strategy. This method fully leverages the reactive power regulation capability of distributed renewable energy sources, reduces the operational frequency of reactive power equipment in substations, and synergizes with the AVC system to achieve optimal power grid operation.